2021
DOI: 10.3390/catal11091089
|View full text |Cite
|
Sign up to set email alerts
|

Noble-Metal-Free NixSy-C3N5 Hybrid Nanosheet with Highly Efficient Photocatalytic Performance

Abstract: The construction of highly efficient, low-cost and noble-metal-free photocatalysts depends on photocatalytic technology. Recently, N-rich C3N5 has been explored as a novel carbon nitride material with a much narrower band gap (~2.2 eV) than that of traditional C3N4 (~2.7 eV). Planting noble-metal-free active sites on C3N5 to improve its photocatalytic activity is of great significance. Herein, 2D NixSy nanosheet is facially loaded on 2D C3N5 using a hydrothermal procedure under a low temperature. Due to the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Long and coworkers fabricated g‐C 3 N 5 /C heterojunctions by copolymerizing 3‐AT and peanut oil under N 2 flow at 600 o C for 2 h. [ 65 ] The other work recorded the Z‐scheme heterojunctions between g‐C 3 N 4 and g‐C 3 N 5 by physically mixing two semiconductors. [ 66 ] They discovered that when combining two nitrogen‐rich carbon‐based materials, the AQY value at 420 nm increased significantly compared to other works at 20.6%. The highest hydrogen generation rate was at 3.33 mmol h −1 g −1 .…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long and coworkers fabricated g‐C 3 N 5 /C heterojunctions by copolymerizing 3‐AT and peanut oil under N 2 flow at 600 o C for 2 h. [ 65 ] The other work recorded the Z‐scheme heterojunctions between g‐C 3 N 4 and g‐C 3 N 5 by physically mixing two semiconductors. [ 66 ] They discovered that when combining two nitrogen‐rich carbon‐based materials, the AQY value at 420 nm increased significantly compared to other works at 20.6%. The highest hydrogen generation rate was at 3.33 mmol h −1 g −1 .…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
“…Recently, Yao and coworkers proposed B‐doped g‐C 3 N 5 (BCN) to produce H 2 . [ 66 ] They investigated the effects of different amounts of B doped into the lattice. They found that nearly 1.3 wt % of B was optimal to accelerate the catalytic performance, as dictated in Figure 22.…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
“…The heterojunctions of Er 3+ /Tb 3+ @BiOBr-g-C 3 N 5 achieved a maximum degradation efficiency of 94.2% after 60 min of Vis-irradiation, while pure g-C 3 N 5 and Er 3+ /Tb 3+ @BiOBr reached approximately 43.8 and 55.2%, respectively. Han et al 95 synthesised a cost-effective hybrid nanosheet composed of mesoporous nickel sulphide (Ni x S y ) and C 3 N 5 via hydrothermal loading at low temperatures. This novel catalyst, which is free of noble metals, exhibits multifunctionality in the removal of nitric oxide (NO).…”
Section: Applications Of C3n5-based Materialsmentioning
confidence: 99%
“…In addition, the g-C 3 N 5 functional materials have also been employed for H 2 evolution and exhibit excellent performance. For example, NixSy-C 3 N 5 [ 63 ], S-Ni(OH) 2 -C 3 N 5 [ 64 ], Pt-C 3 N 5 [ 59 ], CD/MoS 2 /C 3 N 5 [ 65 ], CdS/C 3 N 5 [ 54 ], CdS/C 3 N 5 (CCN) [ 66 ], g-C 3 N 5 /Zn 0 . 5 Cd 0 .…”
Section: Environmental and Energy Applicationsmentioning
confidence: 99%